A CRITICAL ANALYSIS OF FACTORS CONTRIBUTING TO SPEAKING ANXIETY AMONG PHASE C STUDENTS DURING CLASSROOM PRESENTATIONS - Cefi Kurniasih; Ana Andriani; Y. Suyitno; Wakhudin (SOSIOEDUKASI, 2025)
Anxiety about speaking in front of the class is one of the main obstacles to the active participation of Phase C students (grades V and VI) in elementary schools. This study aims to analyze in depth the factors of anxiety about speaking in front of the class in phase C students in one of the elementary school clusters in Adipala District, Cilacap. The descriptive qualitative research method with a case study method, the subjects were phase C students, teachers, and parents. Data were collected through observation, interviews, and documentation studies. Data were analyzed through data condensation, data presentation, and verification of conclusions. Data validity was through source triangulation and technical triangulation. The results of the study indicate that anxiety about speaking in Phase C students is caused by internal and external factors. Internal factors include (1) cognitive/psychological aspects such as fear of making mistakes and feeling inferior; (2) emotional aspects such as nervousness, embarrassment, and mental stress; (3) behavior of avoiding turns or diverting attention; and (4) negative experiences and a tendency towards perfectionism that encourages the desire to always appear perfect. External factors include (1) peer reactions to mistakes that cause embarrassment or fear of being ridiculed; (2) a tense and competitive classroom climate that makes students reluctant to perform; (3) a teacher's corrective communication style without support that creates anxiety; (4) minimal family support that creates a lack of self-confidence; and (5) a lack of interactive learning media that creates a lack of motivation to speak. Overall, the dominant factors of speaking anxiety from an internal aspect are psychological and emotional, while external aspects are the social environment or peers and the classroom climate. Thus, anxiety about speaking in front of the class arises as a result of the interaction between personal factors and the learning environment, so it requires holistic handling through the support of teachers, family, and peers in creating a safe learning atmosphere and building student self-confidence.